Staining potential differences between an infiltrative resin and an esthetic, flowable composite. Issue 5 (4th October 2018) - Silva, Stephanie N.; Reich, Alena M.; DeLeon, Eladio; Schafer, Tara; Rueggeberg, Frederick A.; Fortson, Weston M.
Abstract: Objective: To compare color change magnitude of an infiltrative resin and a flowable composite resin after immersion in commonly consumed beverages. Materials and Methods: Disks (1 × 9 mm) of a flowable composite (Filtek Supreme Ultra Flowable) and a resin‐infiltrative product (Icon) were made. Specimens were dark‐stored in tap water (24 hours). Baseline color parameters (CIE L * a * b *) were obtained using a colorimeter (Easyshade V4, VITA). Specimens were immersed (dark stored, 37°C, 1 week) in commercial beverages: Kool‐Aid, coffee, Coca‐Cola, and tap water (control). Δ E 00 between final and baseline conditions for each material/beverage combination was determined (N = 10/group). Initial analysis of variance indicated significant impact of major factors/interactions on Δ E 00 . Subsequently, t ‐tests between Δ E 00 values of restorative materials within each beverage was performed: alpha 0.05. Results: Kool‐Aid produced the greatest color change for flowable composite, with a Δ E 00 significantly greater than the infiltrative product. No significant Δ E 00 differences were noted between products immersed in coffee, however color parameters causing these differences were not similar. Water or Coca‐Cola immersion showed lowest Δ E 00 values for both materials, considered visually imperceptible: Δ E 00 values <0.8. Conclusions: Color change potential of infiltrative resin or resin composite was highly dependent on beverage type, with no general trends observed in which material was affected more. Clinical Significance: Staining potential of an infiltrative restorative resin differs from that of a filled, flowable composite material on a beverage‐by‐beverage basis. The potential for color change seems not related to the presence or absence of fillers in the restorative material.